Rapid access point of care clinic for transient ischemic attacks and minor strokes. (January 2016) - O'Brien, Elizabeth; Priglinger, Miriam L.; Bertmar, Carin; Day, Susan; Borsodi, Christian; Herkes, Geoffrey; Krause, Martin
Abstract: We present 24 months of prospective data from a new model of care for transient ischemic attacks (TIA) and minor stroke, established at the Royal North Shore Hospital, a tertiary teaching hospital in Sydney, Australia. Prior to 2011, approximately 200 patients were admitted to our emergency department (ED) annually, following presentation with a suspected TIA. These patients had an average length of stay of 5.3 days. Following the establishment of a twice weekly multidisciplinary, one stop, stroke prevention and hospital avoidance clinic, all patients with suspected TIA were investigated and treated as outpatients. There was an average time to clinic from the initial presentation in the ED of 3.9 days. Symptoms that were highly suggestive of TIA were seen in 47% of patients, and an additional 14% had MRI-confirmed acute stroke. In total, 405 patients were referred to the clinic, saving 2146.5 inpatient bed days and approximately AUD$1, 180, 575. Our model of care for patients with suspected TIA provides early access for investigation, treatment and management of the risk factors. The rapid access TIA clinic is highly cost effective and provides a transferable model of care for other health districts with similar patient loads and cost structures.